2015
DOI: 10.2169/internalmedicine.54.3616
|View full text |Cite
|
Sign up to set email alerts
|

Nontuberculous Mycobacterial Lung Disease Accompanied by Organizing Pneumonia

Abstract: We herein report our experience with patients who had nontuberculous mycobacterial lung disease (NTM disease) accompanied by organizing pneumonia (OP). Out of 98 NTM disease patients who had undergone a biopsy or surgical resection, 11 patients had OP that was revealed histologically. After excluding six patients who had OP-related diseases (idiopathic interstitial pneumonia, rheumatoid arthritis, etc.), the remaining five patients were studied. Two of them (a 73-year-old man and a 66-year-old woman) showed co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 21 publications
(21 reference statements)
0
16
0
Order By: Relevance
“…To the best of our knowledge, M. abscessus lung disease accompanying OP has not been described in the English language literature, with the exception of only one case diagnosed with bronchial washing and TBLB (6). Pulmonary M. abscessus infection can present different clinicopathological features according to the various immune responses of the host.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…To the best of our knowledge, M. abscessus lung disease accompanying OP has not been described in the English language literature, with the exception of only one case diagnosed with bronchial washing and TBLB (6). Pulmonary M. abscessus infection can present different clinicopathological features according to the various immune responses of the host.…”
Section: Discussionmentioning
confidence: 95%
“…Pulmonary NTM disease is the most common type of involvement and occurs primarily in patients with preexisting structural lung damage such as emphysema or On the other hand, rare cases with different disease entities have been reported: NTM disease accompanied by histologically proven OP in which patients developed acute or subacute symptoms with infiltrates on chest images, and improved rapidly following treatment with a combination of a corticosteroid and anti-mycobacterial therapy (6,(8)(9)(10). Hamada et al (8) reported a 67-year-old woman with fever and dyspnea; her sputum culture confirmed Mycobacterium intracellulare, and transbronchial lung biopsy (TBLB) revealed OP that showed dramatic clinical improvement clinically with corticosteroid and anti-mycobacterial treatment (clarithromycin, rifampicin, and levofloxacin).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A search of the literature was performed using Medline ( ) with the keywords ‘bronchiolitis obliterans organizing pneumonia OR cryptogenic organizing pneumonia AND lung cancer’ and ‘bronchiolitis obliterans organizing pneumonia OR cryptogenic organizing pneumonia AND case report’. Studies on secondary OP were excluded and a total of 23 studies ( 1 , 2 , 5 , 6 , 8 – 26 ) were retrieved by December 2015.…”
Section: Literature Reviewmentioning
confidence: 99%